Identifying community pharmacists’ skill sets to address the public's needs - Alharbi, Suha (2023)
Introduction: Community pharmacists are skilled healthcare professionals with knowledge and experience that might be put to greater use. Policymakers in the United Kingdom have recognised the potential of community pharmacists as a possible contributor to relieve pressure on other sectors of the NHS. In the past few years, there has been growing support for expanding the role of community pharmacists so that they can provide more advanced services. Reviewing the literature shows that these extended community pharmacy services have positive effects (Boardman and Avery, 2014; Brown et al, 2014; Buchanan et al, 2020; Corlett and Krska, 2016; Ingram et al, 2018), there has been a lack of awareness and utilisation of the CP services among the public. Understanding public views regarding these services is thus beneficial for future community pharmacy service planning and development. Therefore, this PhD aims to identify the public's perceptions of their needs from community pharmacist and developing a skill set to address these needs. Methods: This PhD project consists of three main stages: a scoping review, mixed- methods studies, and finally skill mapping. Firstly, the scoping review was conducted according to Arksey and O'Malley's (2005) framework and Levac et al. (2010). Then, the results were used to inform mixed-methods research using validated online surveys and telephone interviews. This research was undertaken between October 2019 and mid-March 2020 (before and during the COVID-19 pandemic). Data was analysed using descriptive statistics and thematic analysis. Finally, skill mapping was conducted through a framework analysis. Ethical approval was obtained for this study from the research ethics committee at the School of Pharmacy (ref # 015-2019). Results: The scoping review shows that community pharmacy accessibility and convenience are the main reasons behind people using community pharmacy services, while time constraints and funding were real challenges for pharmacists. The review also lists the mechanisms underpinning the successful implementation of community pharmacy services which include acquiring skill and knowledge, accessibility to CP, adequate resources, marketing, collaboration and public trust and confidence. This review offers a hypothesis about how these mechanisms might play out differently in different contexts and account for the success or failure of delivering new services through community pharmacy. From the questionnaire results, the majority of participants had visited a community pharmacy more often than a general practitioner. However, participants’ awareness of the current services delivered in community pharmacy varied. Regarding the expansion of the community pharmacist’s roles, the participants were positive. The services that the public wished to see in community pharmacy included pharmacists as independent prescribers, advice to improve selfcare, and screening services (i.e., illness detection services). With regards to the qualitative results, 12 people participated in semi-structured telephone interviews. Overall, the participants were positive about expanding the community pharmacist’s roles, and emerging codes were mapped to the 7Ps marketing framework: product, price, place, promotion, people, process, and physical evidence. Additionally, the findings of the previous two stages were used to identify the set of skills that community pharmacists will need in the future. Five skills were identified: intrapersonal skills, interpersonal skills, advanced clinical skills, marketing skills, and digital skills. Conclusion: Overall, the participants in this study had a positive attitude towards the changing roles of the community pharmacist. However, the participants perceived several barriers that should be addressed to improve service utilisation and provide tailored services based on their needs. Community pharmacists need to acquire the correct set of skills to ensure that the quality of services provided fits with future need. The proposed set of skills will benefit both the existing and future community pharmacy workforce. This research is useful since it prepares policymakers and pharmacy professional organisations for future planning and development, but consideration should be taken as to how the results should be interpreted since the data was collected before the pandemic and subsequent lockdown in the United Kingdom.